Chlorophenyl thiophene silicon phthalocyanine: Synthesis, two-photon bioimaging-guided lysosome target, and in vitro photodynamic efficacy - Xu, Le; Zhang, Tiantian; Huang, Bingcheng; Zheng, Fangmei; Huang, Yan; Li, Yuyang; Peng, Yiru; Chen, Linying (Frontiers in Pharmacology, 2023)
The development of efficient photosensitizers with high singlet oxygen quantum yield, strong fluorescent emission, excellent photostability and specific ability for targeting organelle is in great demand for the enhancement of PDT treatment efficiency. In this study, a new two-photon photosensitizer chlorophenyl thiophene axially substituted silicon (IV) phthalocyanine (CBT-SiPc) has been designed and synthesized. CBT-SiPc showed specific targeting capability to lysosomes in living cells with good biocompatibility. Furthermore, high 1O2 generation efficiency and high PDT efficiency in MCF-7 breast cancers under irradiation have also been proven. This novel CBT-SiPc reveal great potential in application of lysosome-targeted and two-photon bioimaging guided photodynamic cancer therapy.